2016
DOI: 10.1080/02680513.2016.1190640
|View full text |Cite
|
Sign up to set email alerts
|

The introduction and refinement of the assessment of digitally recorded audio presentations

Abstract: This case study critically evaluates benefits and challenges of a form of assessment included in a final year undergraduate Religious Studies Open University module, which combines a written essay task with a digital audio recording of a short oral presentation. Based on the analysis of student and tutor feedback and sample assignments, this study critically examines how teaching and learning practices linked to this novel form of assessment have been iteratively developed in light of the project findings over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The oral assessments have learner-centered benefits in which the interns can engage and refine translational skills. Learners can self-assess presentation skills by listening to their recordings and in the process reflect on their progress and improve delivery of their message (Gong et al, 2019;Sinclair, 2016). The 2-minute oral assessment did not significantly add to the workload for the intern nor burdensome to evaluate for the preceptor.…”
Section: Key Elements Of the Virtual Internship Resulting In Competen...mentioning
confidence: 93%
“…The oral assessments have learner-centered benefits in which the interns can engage and refine translational skills. Learners can self-assess presentation skills by listening to their recordings and in the process reflect on their progress and improve delivery of their message (Gong et al, 2019;Sinclair, 2016). The 2-minute oral assessment did not significantly add to the workload for the intern nor burdensome to evaluate for the preceptor.…”
Section: Key Elements Of the Virtual Internship Resulting In Competen...mentioning
confidence: 93%
“…Supported by funding from the Higher Education Academy, I critically assessed the use of this form of assessment in the context of this module over the period of two years (2014)(2015), through the analysis of 50 sample assignments and student and teacher questionnaires, completed by 233 students (sent out to 607 students with an overall response rate of 38%) and 17 tutors (sent out to 21 tutors with a response rate of 81%), and designed a toolkit for best practice in the design of this form of assessment in consultation with tutors and students. I drafted this toolkit on the basis of the survey findings and then invited students and tutors to comment on this draft on online forums (Sinclair, 2014;Sinclair, 2016). This toolkit has since been shared with other module teams across the Open University's Arts and Humanities programme and at a range of national and international conferences.…”
Section: Case Study 1: Digitally Recorded Oral Presentationsmentioning
confidence: 99%
“…Collaboration between module teams in the development of this form of assessment and related assessment criteria has aided the formation of a consistent approach to this new form of assessment across the Open University's Arts and Humanities programme. This has enabled students to build on their tutors' feedback (and 'feed forward') in the development of their oral presentation skills across different modules (see also : Sinclair, 2016). This highlights the need to carefully manage the implementation of new forms of assessment, particularly when a shared understanding of the aims and purpose of this form of assessment need to be reached across different modules and tutors.…”
Section: Case Study 1: Digitally Recorded Oral Presentationsmentioning
confidence: 99%
“…Martin-Monje, Barcena and Ventura (2013), reporting on a similar activity for ESL students in a MOOC course, found that a high proportion of students did not engage with the activity, probably because of the amount of effort involved. A study by Sinclair (2016) found that there were some benefits to students receiving lecturer feedback on audio files of their presentations, but again, many students had technical difficulties, and a common reaction was that students felt the experience was difficult without an audience. The lack of research describing situations where distance students receive individual feedback for their (audio or audiovisual) recordings of oral presentations suggests that this type of activity is rare.…”
Section: The Role Of Oral Presentation Skills In Online Educationmentioning
confidence: 99%